PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN ONLINE BERBASIS GESCHOOL TERHADAP MOTIVASI BELAJAR MATEMATIKA PESERTA DIDIK KELAS VII SMP NEGERI 20 PADANG - LATIFA TUNSADIAH (Departemen Matematika, 2022)
During the Covid-19 pandemic, many schools are taking advantage of online educational resources. Utilization of multimedia technology can support the method of education that is not perfect. Utilizing a quality mathematics education program like Geschool is one way to enhance student learning outcomes, particularly in mathematics. The goal of this research was to identify and evaluate how the learning environment at SMP Negeri 20 Padang affected students' willingness to learn mathematics. Pre-experimental research with a one-shot case study project is what this kind of study entails. The object of research is 32 students of class VII.8 SMP Negeri 20 Padang. Analysis of research data reveals a correlation coefficient, according to the findings (0.362 > 0.2335) with a significance level of 5% and an efficiency of 13%. The findings of this study show that the SMP Negeri 20 Padang's utilization of online learning resources greatly increases students' enthusiasm to learn mathematics. Keywords– Learning Media, Geschool, Mathematics Learning, Learning Motivation